Care-Arrangements and Parental Well-Being during the COVID-19 Pandemic in Germany - Gundula Zoch; Ann-Christin Bächmann; Basha Vicari (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2020)
This study examines the short-term consequences for care-arrangements and resulting changes in well-being among parents, who were affected by the closure of schools and institutional child-care during the COVID-19 pandemic in Germany. By applying multinomial logistic regression models to novel panel data from the National Educational Panel Study (NEPS-Corona_CAWI_C2), the study finds that mothers play a key role in the ad-hoc care-arrangements during the COVID-19 pandemic confirming the traditional division of family work in German couples. Moreover, the results illustrate the importance of working conditions, especially the possibility of remote work, in the bargaining processes of parents. However, contrary to our assumptions, parents' well-being was not influenced by the chosen care-arrangement during the first months of the crisis. – – Diese Studie untersucht die kurzfristigen Folgen für die Betreuungsarrangements von Eltern, die während der COVID-19-Pandemie in Deutschland von der Schul- und Kita-Schließung betroffen waren und die daraus resultierenden Veränderungen im ihrem Wohlbefinden. Mit multinomialen logistischen Regressionen, angewendet auf neue Paneldaten des Nationalen Bildungspanels (NEPS-Corona_CAWI_C2) findet die Studie, dass Mütter eine Schlüsselrolle in den Ad-hoc-Betreuungsarrangements während der COVID-19-Pandemie spielen, was die traditionelle Aufteilung der Familienarbeit bei deutschen Paaren bestätigt. Darüber hinaus veranschaulichen die Ergebnisse die Bedeutung der Arbeitsbedingungen, insbesondere die Möglichkeit des Homeoffice, für den Verhandlungsprozess der Eltern. Entgegen unseren Annahmen wurde das Wohlergehen der Eltern in den ersten Krisenmonaten jedoch nicht durch das gewählte Betreuungsarrangement beeinflusst.
Keywords: J13; J22; I31; 330; Childcare; gender division of labour; well-being; COVID-19; NEPS-C